Analysis of Rice Field Farming Income in Ogogasang Village, Dondo District, Tolitoli Regency: ANALISIS PENDAPATAN USAHATANI PADI SAWAH DI DESA OGOGASANG KECAMATAN DONDO KABUPATEN TOLITOLI - Nurlena Nurlena; Edi Yanto (STIE MUJAHIDIN TOLITOLI, 2025)
This study aims to determine the income of rice field farming. Respondents were randomly selected for 10% with a total of 17 people. The analysis method used is qualitative. The results of the study showed that the total income obtained from 17 rice farmers in Ogogasang Village amounted to Rp. 201,826,326 with an average amount of Rp.7,923,963/farmer, and the amount of production in one planting season was 23,825 kilograms/one year with an average production of 1,401 kilograms and a total amount of revenue of Rp. 269,180,000/one year with an average income of Rp. 15,834,118/farmer/one year and the total amount of costs incurred amounting to Rp.67,353,674/one year with an average of Rp.3,961,981/farmer/one year.